Pendekatan Pedagogis dalam Pemikiran Thomas Aquinas: Perspektif Antropologi: Pendekatan Pedagogis dalam Pemikiran Thomas Aquinas: Perspektif Antropologi - Neonnub, Patricius (Undiksha, 2025)
This study examines the pedagogical principles embedded in the thought of Thomas Aquinas through an anthropological lens, emphasizing their relevance to contemporary education. Grounded in Aquinas's theological anthropology and metaphysical realism, the paper explores three key dimensions: (1) the human learner as a rational and volitional being oriented toward truth and virtue ; (2) the teacher’s role as a facilitator of knowledge rather than its cause ; and (3) the relational and dialogical nature of education as a path to moral and intellectual formation (Torrell; Pieper). Aquinas’s epistemology, which integrates sensory experience with intellectual abstraction, supports a constructivist approach to learning, while his emphasis on disputatio fosters critical inquiry. The study argues that Aquinas’s holistic model—uniting truth-seeking, virtue cultivation, and relational pedagogy—offers a robust alternative to reductionist educational paradigms, addressing modern challenges such as moral relativism and dehumanized instruction. Ultimately, his vision reaffirms education as a transformative journey toward wisdom and beatitude.